The RAND security cooperation prioritization and propensity matching tool - Paul, Christopher, 1971-; Nixon, Michael J. (Michael Joseph); Peterson, Heather; Grill, Beth; Yeats, Jessica M. (RAND, 2013)
Security cooperation is the umbrella term used to describe a wide range of programs and activities with such goals as building relationships between the United States and partner countries, developing these countries' security capabilities, and facilitating contingency and peacetime access by U.S. forces. With increased pressure on defense spending, the scope and budget for these activities are likely to decrease. Therefore, it will be important for the U.S. Department of Defense to scrutinize and, perhaps, reevaluate current and proposed security cooperation efforts, ensuring that expected benefits align with costs and corresponding policy priorities. Recent RAND research identified practices and contextual factors associated with greater or lesser degrees of success in security cooperation, using 29 historical case studies of U.S. efforts to build partner capacity since the end of the Cold War. The RAND Security Cooperation Prioritization and Propensity Matching Tool applies these findings and results from other existing research to all current and potential security cooperation partners. This customizable diagnostic tool, built in Microsoft Excel®, will help planners preliminarily identify mismatches between the importance of a country to U.S. interests, funding for initiatives, and the propensity for successful U.S. security cooperation with a given country. For each of the world's 195 countries, the tool produces an overall security cooperation propensity score. Planners can then compare these scores with available funding and security cooperation priorities. The tool has the virtues of being systematic, being based on global data, and not relying on subjective assessments. Strategic thinking and nuanced understanding of individual countries remain important, but the tool is useful in helping to identify which countries to scrutinize.